Evolutionary Characteristics and Driving Capacity of Ecological Zoning in Middle and Lower Reaches of Hanjiang River Basin Based on Ecosystem Service Functions - Liang Huaqiu; Li Song (Shuitu baochi tongbao)
[Objective] The evolution characteristics and driving capacity of ecological zones in the middle and lower reaches of the Hanjiang River basin were studied in order to provide a scientific basis for the sustainable development of the water ecological environment of this region. [Methods] We used the InVEST model, clustering, and correlation analysis to conduct a multi-year analysis of ecosystem service changes and zoning characteristics based on water environment-related ecosystem services, and to study the association characteristics of ecosystem services and environmental variables within each ecological zoning transfer area. [Results] ① In 2010, 2015, and 2020, the dominant ecological zoning areas were the third, third, and second category areas, respectively, with area shares of 70.54%, 72.92%, and 45.53%. The second category areas had greater water content and soil conservation intensity than the third category areas. ② Correlation analysis showed that rainfall changes were significantly correlated with changes in water conservation and soil conservation intensity. Changes in the areas of agricultural land and construction land for each land use type were significantly correlated with changes in ecosystem services. ③ Regarding the contribution rate of explanatory variables in the areas where ecological zoning shifts occurred, the areas with larger explanatory rates of rainfall changes were mainly located in the central and southern parts of the study area, and the areas with larger explanatory rates of land use changes were mainly located in the western and northwestern parts of the study area. [Conclusion] Rainfall changes had a greater impact on ecosystem services and ecological zoning changes than land use changes. By identifying the key drivers of ecological zoning changes, the stability of ecosystems can be enhanced in the future with targeted optimization of land use type layout or construction of green and gray infrastructure.